Prognostic implications of CT/MRI LI‐RADS in hepatocellular carcinoma: State of the art and future directions. (25th July 2022) - Wei, Hong; Yang, Ting; Chen, Jie; Duan, Ting; Jiang, Hanyu; Song, Bin
Abstract: Hepatocellular carcinoma (HCC) is the fourth most lethal malignancy with an increasing incidence worldwide. Management of HCC has followed several clinical staging systems that rely on tumour morphologic characteristics and clinical variables. However, these algorithms are unlikely to profile the full landscape of tumour aggressiveness and allow accurate prognosis stratification. Noninvasive imaging biomarkers on computed tomography (CT) or magnetic resonance imaging (MRI) exhibit a promising prospect to refine the prognostication of HCC. The Liver Imaging Reporting and Data System (LI‐RADS) is a comprehensive system for standardizing the terminology, techniques, interpretation, reporting and data collection of liver imaging. At present, it has been widely accepted as an effective diagnostic system for HCC in at‐risk patients. Emerging data have provided new insights into the potential of CT/MRI LI‐RADS in HCC prognostication, which may help refine the prognostic paradigm of HCC that promises to direct individualized management and improve patient outcomes. Therefore, this review aims to summarize several prognostic imaging features at CT/MRI for patients with HCC; the available evidence regarding the use of LI‐RDAS for evaluation of tumour biology and clinical outcomes, pitfalls of current literature, and future directions for LI‐RADS in the management of HCC.